XI. Yüzyılda Orta Anadolu'ya Ermeni Göçleri - Gürbüz, Osman (Dinî araştırmalar, 2004)
The Armenian people who had lived in Van and Ani in the first part of the eleventh century immigrated to Central Anatolia. During this time, the Turkish raids were targetting the East Anatolia. Some researchers claim that the Armenian immgrations took place due to the attacks carried out by the Turks. However, this claim is not consistent with the historical evidence and truths. The things that forced the Armenians to immigrate to Central Anatolia was the Byzantines and this was a traditional policy of the Byzantines. The Turkish attacks in the East Anatolia provided a proper offortunity for the Byzantines to exploit these attacks. Otherwise, the two events (Turkish attacks and Armenian immgrations) took place synchronicly are not cause and effect of each other